Investigating B cell biology in CASPR2-antibody encephalitis - Sun, B (2022)
CASPR2-antibody encephalitis is an increasingly recognised cause of autoimmune encephalitis and part of a growing body of neuroglial antibody-mediated diseases. At its core, B cells are responsible for all autoantibody production; however, their origin and the pathogenicity of their secreted CASPR2 autoantibodies remains poorly understood. By applying bulk and single-cell cultures, along with molecular approaches, I sought to characterise the underling B cell immunobiology of CASPR2- antibody encephalitis.